Comparison between two-level and three-level DC/DC converters - Jiang, Tianche; Chen, Mingshan (My University, 2024)
Abstract As automotive industry is developing rapidly, electric vehicles (EVs) have became a popular idea for green transportation due to its zero tailpipe emissions. One of the key parts on the EV board is the step-down DC/DC converter which is used to transfer power from high-voltage side battery to low-voltage side battery. To protect batteries on both sides, this DC/DC converter is always selected as isolated buck converter. This thesis project simulates, analysis and compares two-level and three-level isolated topologies, which are phase-shifted full bridge (PSFB) and T-Type converters in terms losses, efficiency and cost. In addition, since semiconductor technology is also growing quite fast, the new switching technology is used in selected topologies to check the difference between new switching device technology and traditional switching devices. Firstly, the operation principles of different topologies with voltage, current waveform and parameter selection are presented, which is followed by the theoretical comparisons about transformer turns ratio, voltage stress, current waveform with rms current, MOSFET losses, transformer design and its losses calculation. In order to have more realistic results and a fair comparison, simulation of different topologies with same input and output voltage is done with PSpice. Then, the data exported from simulations are used to calculate MOSFET losses and efficiency while the transformer loss calculation is based on both simulation data and real model. The final results show that PSFB has high efficiency while all topologies are operating with the same switching techniques, but T-Type converter has potential to increase efficiency by replacing the middle bridge SiC MOSFETs with Si MOSFETs.
Keywords: DC/DC converter, Phase Shifted Full Bridge converter (PSFB), T-Type converter, Zero-Voltage switching (ZVS); DC/DC converter; Phase Shifted Full Bridge converter (PSFB); T-Type converter; Zero-Voltage switching (ZVS)